“Dynamics of chromophoric dissolved organic matter in the Atlantic Ocean: unravelling province-dependent relationships, optical complexity, and environmental influences” - Sabbaghzadeh, Bita; Uher, Guenther; Upstill-Goddard, Robert (Frontiers in Marine Science, 2024)
We report on the spatial distributions and optical characteristics of chromophoric dissolved organic matter (CDOM) in the sea surface microlayer (SML) and in subsurface seawater (SSW) across a range of Atlantic Ocean biogeochemical provinces during two cruises of the UK Atlantic Meridional Transect program (AMT24 and AMT25). We measured the CDOM absorption coefficient at 300 nm, aCDOM(300), and determined CDOM spectral slopes across two UV wavelength ranges: S1 (275-295 nm) and S2 (350-400 nm). We used spectral slope ratios (SR: S1/S2) to infer CDOM source characteristics and transformation history. During both cruises, SML aCDOM(300) was highest in the Northern Hemisphere, particularly in the North Atlantic Drift Region (NADR). CDOM was always enriched in the SML, with enrichment factors (SML aCDOM(300) / SSW aCDOM(300)) ranging from 1.03 to 2.00, reflecting preferential accumulation of CDOM in the SML. We also found a significant inverse correlation between aCDOM(300) and S1 in both the SML (Spearman's rank correlation coefficient, r 2 = -0.75, p < 0.001, n = 114) and water column profiles down to 500 m (r 2 = -0.74, p < 0.001, n = 845).Biogeochemical province-dependent variations in the relationships between CDOM and chlorophyll a were also observed. In high-latitude regions, elevated aCDOM(300) and low SR values indicated a dominance of terrestrially-derived CDOM, whereas oligotrophic subtropical areas showed lower aCDOM(300) and higher SR values, suggestive of aged, refractory, and photodegraded biologicallyderived CDOM. Taken together, these findings reveal a complexity of drivers affecting CDOM distributions and spectral properties, which may limit the use of CDOM in predictive relationships in the oceans. However, for chlorophyll a, its potential use as a CDOM proxy may prove most successful in open ocean regions devoid of terrestrial inputs, where biological production predominates.